A carbon-coated iron-molybdenum catalyst and its preparation method and application
By forming a graphene carbon layer on the surface of the iron-molybdenum catalyst and adding surfactant, the problems of poor catalyst stability and short service life are solved, and the effect of improving mechanical strength, wear resistance and catalytic activity is achieved.
Patent Information
- Application Number
- CN202411985792.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
During the use of existing iron-molybdenum catalysts, there are problems such as easy agglomeration of active phases, easy sublimation and loss of Mo elements, and insufficient mechanical strength and wear resistance of the catalyst, resulting in poor stability and short service life.
By forming a graphene carbon layer on the surface of the metal iron-molybdenum catalyst, oxidation, agglomeration and loss are prevented, and surfactant is added to disperse the catalyst particles, a carbon-coated iron-molybdenum catalyst is prepared.
It improves the mechanical strength and wear resistance of the catalyst, enhances stability, extends service life, and optimizes the catalytic reaction process, and improves the conversion rate of formaldehyde.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a carbon-coated iron-molybdenum catalyst and a preparation method and application thereof. Background Art
[0002] As an important industrial raw material, formaldehyde is widely used in various fields. The iron-molybdenum process for producing formaldehyde can greatly reduce the use of fossil energy due to its low reaction temperature, and has the advantages of high reaction conversion rate and high reaction efficiency. However, as the key active ingredient of formaldehyde catalyst, molybdenum has poor stability in the catalyst. The sublimation loss of molybdenum will lead to a decrease in the performance of the formaldehyde catalyst, thereby affecting the formaldehyde conversion rate and the life of the formaldehyde catalyst.
[0003] CN112657504 proposes a coating catalyst for preparing formaldehyde by methanol oxidation using an iron-molybdenum method and a preparation method thereof, wherein a composite active phase structure with a high specific surface area CuMoO4 phase as a matrix and a matrix surface distributed from the inside to the outside in sequence by MoO3 phase and Fe2(MoO4)3 phase is prepared, and the active substance is coated on the surface of an inert spherical carrier by a rolling coating process to prepare a spherical coating catalyst, thereby achieving efficient utilization of active metals and effectively inhibiting the loss of Mo elements and the generation of inactive phases during the use of the catalyst. CN113368863 provides a method for preparing an eggshell iron-molybdenum catalyst containing silicon dioxide, wherein silicon dioxide is coated on the surface of the active center of the iron-molybdenum catalyst by a liquid spray coating or impregnation method, thereby alleviating the loss of molybdenum, thereby improving the activity and service life of the catalyst. However, when silicon dioxide is coated by a liquid spray coating or impregnation method, there may be a problem of insufficient uniformity of the coating layer, resulting in poor mechanical properties and wear resistance of the catalyst and reduced stability. CN115947650 provides a process for producing formaldehyde by oxidizing methanol. The process introduces carbon and gold elements and introduces a high melting point molybdenum carbide structure to avoid the loss of molybdenum and thus shorten the life of the catalyst. However, this method increases the production cost of the catalyst.
[0004] The above methods for improving the preparation process of Fe-Mo-based formaldehyde catalysts have improved certain aspects of catalyst performance, but each method still has shortcomings and is difficult to comprehensively solve the following problems existing in current catalysts: (1) The active phase is easy to agglomerate, and the effective utilization rate of active metals is insufficient; (2) During use, the Mo element is easy to sublimate and lose, and inactive substances are gradually generated in the catalyst, causing the catalyst to be easily deactivated; (3) The mechanical strength and wear resistance of the catalyst are insufficient, resulting in poor catalyst stability and short service life. Summary of the invention
[0005] The object of the present invention is to provide a carbon-coated iron-molybdenum catalyst and a preparation method and application thereof. The method provided by the present invention generates a graphene carbon layer on the surface of the metal iron-molybdenum catalyst to prevent the metal iron-molybdenum catalyst from being oxidized, agglomerated, lost, and other problems, thereby improving the mechanical strength and wear resistance of the catalyst, thereby improving the stability of the catalyst and extending its service life. The added surfactant can effectively disperse the metal iron-molybdenum catalyst particles, prevent them from agglomerating and precipitating, and improve the effective utilization rate of the active metal.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing a carbon-coated iron-molybdenum catalyst, which is characterized by comprising the following steps:
[0008] (1) mixing deionized water and nitric acid solution to obtain a mother liquor;
[0009] Under heating and stirring conditions, adding a molybdate solution and an iron salt solution dropwise to the mother liquor, and adjusting the pH value of the system to obtain a suspension;
[0010] (2) subjecting the suspension obtained in step (1) to aging and a first post-treatment in sequence to obtain a precursor;
[0011] calcining the precursor to obtain iron-molybdenum oxide;
[0012] (3) After mixing the carbon source and the solvent, adding the acidic solution, and performing a first stirring treatment to obtain a carbon source solution;
[0013] The carbon source solution is mixed with a surfactant and the iron-molybdenum oxide obtained in step (2), and pH is adjusted, a second stirring treatment is performed, and pyrolysis is performed in sequence to obtain a pyrolysis product;
[0014] The pyrolysis product is mixed with deionized water, and a third stirring treatment and a second post-treatment are performed in sequence to obtain a carbon-coated iron-molybdenum catalyst.
[0015] Preferably, the pH of the mother liquor in step (1) is 1 to 6; and the temperature of the heating and stirring is 25 to 90°C.
[0016] Preferably, the concentrations of the molybdate solution and the iron salt solution in step (1) are independently 0.1-1.0 mol / L; the molar ratio of molybdenum in the molybdate solution to iron in the iron salt solution is (0.3-4.5):1.
[0017] Preferably, the calcination temperature in step (2) is 200-650° C., and the calcination time is 2-7 hours.
[0018] Preferably, the carbon source in step (3) is at least one of sugars, alcohols, organic acids, aldehydes, polystyrene, polyphenols and melamine.
[0019] Preferably, in step (3), the mass ratio of iron-molybdenum oxide to carbon source aqueous solution is (0.1-1):1.
[0020] Preferably, in step (3), adjusting the pH is to add an alkali solution to adjust the pH of the system to 5-9; the alkali in the alkali solution is carbonate, phosphate, NaOH or NH3·H2O.
[0021] Preferably, the pyrolysis temperature in step (3) is 600-1000° C., and the pyrolysis time is 1-12 h.
[0022] The present invention also provides a carbon-coated iron-molybdenum catalyst prepared by the preparation method described in the above technical solution.
[0023] The present invention also provides the use of the carbon-coated iron-molybdenum catalyst described in the above technical solution in the preparation of formaldehyde.
[0024] The invention provides a method for preparing a carbon-coated iron-molybdenum catalyst. First, iron-molybdenum oxide is prepared, and then the iron-molybdenum oxide and a carbon source solution are mixed so that the carbon source can be uniformly attached to the surface of the iron-molybdenum oxide. A carbon-coated iron-molybdenum catalyst is formed through pyrolysis. A graphene carbon layer generated on the surface of the metal iron-molybdenum catalyst builds a layer of "armor" for the internal metal iron-molybdenum catalyst, which can effectively protect the internal metal catalyst and prevent it from being oxidized, agglomerated, lost, and other problems, thereby improving the mechanical strength and wear resistance of the catalyst, thereby improving the stability of the catalyst and extending its service life. At the same time, this graphene carbon layer can also have a positive effect on the adsorption mode of reactant molecules on the active sites of the catalyst, thereby further optimizing the catalytic reaction process and improving the conversion rate of formaldehyde and the service life of the catalyst. The addition of a surfactant can effectively disperse the metal iron-molybdenum catalyst particles, prevent them from agglomerating and precipitating, improve the effective utilization rate of the active metal, and is also conducive to the carbon layer being uniformly coated on the catalyst surface. DETAILED DESCRIPTION
[0025] The present invention provides a method for preparing a carbon-coated iron-molybdenum catalyst, which is characterized by comprising the following steps:
[0026] (1) mixing deionized water and nitric acid solution to obtain a mother liquor;
[0027] Under heating and stirring conditions, adding a molybdate solution and an iron salt solution dropwise to the mother liquor, and adjusting the pH value of the system to obtain a suspension;
[0028] (2) subjecting the suspension obtained in step (1) to aging and a first post-treatment in sequence to obtain a precursor;
[0029] calcining the precursor to obtain iron-molybdenum oxide;
[0030] (3) After mixing the carbon source and the solvent, adding the acidic solution, and performing a first stirring treatment to obtain a carbon source solution;
[0031] The carbon source solution is mixed with a surfactant and the iron-molybdenum oxide obtained in step (2), and pH is adjusted, a second stirring treatment is performed, and pyrolysis is performed in sequence to obtain a pyrolysis product;
[0032] The pyrolysis product is mixed with deionized water, and a third stirring treatment and a second post-treatment are performed in sequence to obtain a carbon-coated iron-molybdenum catalyst.
[0033] In the present invention, unless otherwise specified, the raw materials used are conventional commercial products in the art.
[0034] The present invention mixes deionized water and nitric acid solution to obtain a mother liquor.
[0035] In the present invention, the concentration of the nitric acid solution is preferably 10% to 75%.
[0036] In the present invention, the pH of the mother solution is preferably 1 to 6. The present invention controls the precipitation and dispersion process of the metal elements by controlling the pH of the mother solution, thereby regulating the morphology and activity of the synthesized catalyst.
[0037] After the mother liquor is obtained, the present invention drips the molybdate solution and the iron salt solution into the mother liquor under heating and stirring conditions, and simultaneously adjusts the pH of the system to obtain a suspension.
[0038] In the present invention, the temperature of the heating and stirring is preferably 25 to 90°C.
[0039] In the present invention, the concentrations of the molybdate solution and the iron salt solution are independently preferably 0.1 to 1.0 mol / L; the molar ratio of molybdenum in the molybdate solution to iron in the iron salt solution is preferably (0.3 to 4.5): 1. The present invention controls the molar ratio of molybdenum in the molybdate solution to iron in the iron salt solution to regulate the stability, activity and selectivity of the catalyst.
[0040] In the present invention, the pH adjustment system is preferably added with a nitric acid solution with a concentration of 10% to 30% and an ammonia solution with a concentration of 5% to 20%, and the pH value of the system is controlled to be 1 to 6. The present invention controls the precipitation and dispersion process of the metal elements by controlling the pH value of the system, thereby regulating the morphology and activity of the synthesized catalyst.
[0041] The obtained suspension is subjected to aging and a first post-treatment in sequence to obtain a precursor.
[0042] In the present invention, the aging is preferably carried out by stirring at 25 to 120° C. for 2 to 24 hours. The present invention adjusts the number and distribution of active sites on the catalyst surface through aging.
[0043] In the present invention, the first post-treatment is preferably: filtering, washing, drying and grinding the aged product in sequence to obtain a precursor.
[0044] The present invention has no special restrictions on the filtering and washing methods, and the technical solutions known in the art can be used. The present invention has no special restrictions on the drying method, and the residual reagent can be removed. In the present invention, the particle size of the precursor obtained by grinding is preferably 250 to 350 μm.
[0045] After obtaining the precursor, the present invention calcines the precursor to obtain iron-molybdenum oxide.
[0046] In the present invention, the calcination temperature is preferably 200-650° C., and the calcination time is preferably 2-7 hours. The present invention controls the calcination temperature and time within the above range to regulate the specific surface area and pore volume of the catalyst.
[0047] In the present invention, after the carbon source and the solvent are mixed, an acidic solution is added, and a first stirring treatment is performed to obtain a carbon source solution.
[0048] In the present invention, the carbon source is preferably at least one of sugars, alcohols, organic acids, aldehydes, polystyrene, polyphenol, and melamine; the sugar is preferably at least one of sucrose, glucose, starch, and chitosan; the organic acid is preferably at least one of citric acid, oxalic acid, and acetic acid; the aldehyde is preferably at least one of formaldehyde and acetaldehyde.
[0049] In the present invention, the solvent is preferably at least one of deionized water and alcohol solvents; the alcohol solvent is preferably at least one of methanol and ethanol.
[0050] In the present invention, the mass ratio of the carbon source to the solvent is preferably (0.01-0.1):1.
[0051] In the present invention, the acid in the acidic solution is preferably one of acetic acid, hydrochloric acid and nitric acid; the concentration of the acid in the acidic solution is preferably 10% to 50%. In the present invention, the mass ratio of the carbon source to the acidic solution is preferably 1:(5 to 20). The present invention ensures full utilization of the carbon source and optimizes the performance of the catalyst by controlling the mass ratio of the carbon source to the acidic solution.
[0052] In the present invention, the time of the first stirring treatment is preferably 10 to 16 hours.
[0053] After obtaining the carbon source solution and the iron-molybdenum oxide, the present invention mixes the carbon source solution with a surfactant and the iron-molybdenum oxide, and sequentially performs pH adjustment, a second stirring treatment and pyrolysis to obtain a pyrolysis product.
[0054] In the present invention, the surfactant is preferably at least one of CTAB, stearic acid, lauric acid, and sodium dodecyl sulfate. In the present invention, the amount of the surfactant added is preferably 0.1 to 5 wt% of the iron-molybdenum oxide. By adding the surfactant, the present invention can effectively disperse the metal iron-molybdenum catalyst particles, prevent them from agglomerating and precipitating, improve the effective utilization rate of the active metal, and also facilitate the carbon layer to be evenly coated on the catalyst surface.
[0055] In the present invention, the mass ratio of the iron-molybdenum oxide to the carbon source aqueous solution is preferably (0.1-1):1.
[0056] In the present invention, the pH is preferably adjusted by adding an alkali solution to adjust the pH of the system to 5 to 9; the alkali in the alkali solution is preferably carbonate, phosphate, NaOH or NH3·H2O. The present invention adjusts the pH to promote uniform attachment of the carbon source by changing the surface charge of the catalyst, optimizes the surfactant behavior to prevent the carbon source from agglomerating and forming a uniform adsorption layer, and appropriately controls the pH to affect the growth rate, morphology and structure of graphene, thereby achieving a uniform coating effect.
[0057] In the present invention, the second stirring treatment time is preferably 10 to 16 hours.
[0058] In the present invention, the pyrolysis temperature is preferably 600-1000°C, and the pyrolysis time is preferably 1-12 hours. The present invention controls the pyrolysis temperature and time to promote the formation of graphene and optimize the structure and performance of the catalyst to improve the catalytic activity, selectivity and stability, while achieving controllable preparation of the catalyst to meet the needs under different reaction conditions.
[0059] After obtaining the pyrolysis product, the present invention mixes the pyrolysis product with deionized water, and sequentially performs a third stirring treatment and a second post-treatment to obtain a carbon-coated iron-molybdenum catalyst.
[0060] In the present invention, the time of the third stirring treatment is preferably 10 to 16 hours.
[0061] In the present invention, the second post-treatment preferably includes suction filtration, washing and vacuum drying. The present invention has no special restrictions on the method of suction filtration, and solid-liquid separation can be achieved. The present invention has no special restrictions on the method of washing, and residual reagents can be removed. The present invention has no special restrictions on the method of vacuum drying, and residual reagents can be removed.
[0062] The present invention also provides a carbon-coated iron-molybdenum catalyst prepared by the preparation method described in the above technical solution.
[0063] The present invention also provides the use of the carbon-coated iron-molybdenum catalyst described in the above technical solution in the preparation of formaldehyde.
[0064] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0065] Example 1
[0066] A method for preparing a carbon-coated iron-molybdenum catalyst, comprising the following steps:
[0067] (1) In a glass stirred tank, add 10% nitric acid solution to 100 g of deionized water and mix well to obtain a mother solution with a pH of 2.5;
[0068] The mother liquor was heated to 80° C., and then 200 mL of a 0.1 mol / L ammonium molybdate solution and 200 mL of a 0.1 mol / L ferric nitrate solution were added dropwise to the mother liquor at 80° C. with stirring, and a 10% nitric acid solution and a 20% ammonia solution were added to adjust the pH of the system to 2.5, and the addition was completed to obtain a suspension;
[0069] (2) The suspension obtained in step (1) is aged at 35° C. for 24 h under stirring, and then filtered, washed and dried in sequence, and ground to obtain a precursor with an average particle size of 250 μm;
[0070] The precursor is calcined at 400° C. for 4 hours to obtain iron-molybdenum oxide;
[0071] (3) 4 g of glucose as a carbon source was mixed with 100 mL of deionized water solvent, and 1 mL of acetic acid was added. The mixture was stirred overnight (12 h) to obtain a carbon source solution.
[0072] The mass ratio of the carbon source to the solvent is 0.02:1; the acidic solution is an aqueous solution of acetic acid with a concentration of 10%;
[0073] The carbon source solution is mixed with a CTAB surfactant and the iron-molybdenum oxide obtained in step (2), and an ammonia alkaline solution is added to adjust the pH of the system to 9, and a second stirring treatment is performed for 10 hours, and pyrolysis is performed at 800° C. for 2 hours, and the temperature is naturally lowered to obtain a black solid powder pyrolysis product;
[0074] The mass ratio of the iron-molybdenum oxide to the carbon source aqueous solution is 0.15:1; the added amount of the surfactant accounts for 1wt% of the iron-molybdenum oxide;
[0075] The pyrolysis product was mixed with deionized water, stirred overnight (12 h), and then filtered, washed and vacuum dried in sequence to obtain a carbon-coated iron-molybdenum catalyst.
[0076] Example 2
[0077] A carbon-coated iron-molybdenum catalyst was prepared according to the method of Example 1. The difference from Example 1 was that when the ammonium molybdate solution and the ferric nitrate solution were added dropwise to the mother liquor, a 10% nitric acid solution and a 20% ammonia solution were added simultaneously to adjust the pH of the system to 3. After the addition was completed, a suspension was obtained.
[0078] Example 3
[0079] A carbon-coated iron-molybdenum catalyst was prepared according to the method of Example 1. The difference from Example 1 was that when the ammonium molybdate solution and the ferric nitrate solution were added dropwise to the mother liquor, a 10% nitric acid solution and a 20% ammonia solution were added simultaneously to adjust the pH of the system to 3.5. After the addition was completed, a suspension was obtained.
[0080] Example 4
[0081] A carbon-coated iron-molybdenum catalyst was prepared according to the method of Example 1. The difference from Example 1 was that when the ammonium molybdate solution and the ferric nitrate solution were added dropwise to the mother liquor, a 10% nitric acid solution and a 20% ammonia solution were added simultaneously to adjust the pH of the system to 5. After the addition was completed, a suspension was obtained.
[0082] Comparative Example 1
[0083] The preparation steps of the iron-molybdenum catalyst are as follows:
[0084] An iron-molybdenum catalyst was prepared according to Example 1 as an iron-molybdenum catalyst.
[0085] Performance Testing
[0086] The corresponding catalysts prepared in Examples 1 to 4 and Comparative Example 1 were used to catalyze methanol to prepare formaldehyde. The specific steps were as follows: the activity and selectivity of the catalyst were evaluated using a fixed bed reaction device. A mixture of air with a flow rate of 80 mL / min and nitrogen with a flow rate of 70 mL / min was introduced into a methanol raw material bottle with a constant temperature control device to remove methanol vapor and prepare a mixed raw gas. The methanol content in the mixed gas was monitored by gas chromatography and was about 6.9%. The mixed raw gas was preheated in a preheating furnace and then introduced into a reactor for reaction. The reaction temperature was 300°C, the catalyst dosage was 1.4 mL, and the air velocity was 6675 h -1The reaction tube is an iron tube with an inner diameter of 8 mm, and high-temperature ceramics are filled at both ends. The constant temperature section is a catalyst bed. The composition of the reaction gas is analyzed online by two gas chromatographs with hydrogen flame detectors (FID). Among them, CO and CO2 are separated by TDX-01 chromatographic columns and converted into methane in a micro-methanization furnace at 360°C for detection and analysis. The column temperature is 100°C and the detector temperature is 260°C. Methanol and other products are analyzed by another chromatograph with an HP-INNOWAX capillary column, with a column temperature of 40°C and a detector temperature of 260°C. The test results are shown in Table 1.
[0087] Table 1 Performance statistics of the corresponding catalysts prepared in Examples 1 to 4 and Comparative Example 1 for catalyzing the preparation of formaldehyde from methanol
[0088] sample Methanol conversion rate Formaldehyde yield life Example 1 97.3% 94.6% 769 days Example 2 98.2% 95.4% 880 days Example 3 97.9% 95.0% 821 days Comparative Example 1 96.3% 92.1% 500 days
[0089] In summary, compared with Comparative Example 1, Examples 1 to 3 use the method provided by the present invention to wrap a layer of graphene around the iron-molybdenum catalyst, and the life of the catalyst prepared is significantly improved. The present invention builds a layer of "armor" for the internal metal iron-molybdenum catalyst through carbon coating, which can effectively protect the internal metal catalyst, prevent it from oxidation, agglomeration and loss, improve the mechanical strength and wear resistance of the catalyst, thereby improving the stability of the catalyst and extending its service life. At the same time, this layer of graphene carbon layer can also have a positive effect on the adsorption mode of the reactant molecules on the active sites of the catalyst, thereby further optimizing the catalytic reaction process, improving the conversion rate of formaldehyde and the service life of the catalyst; the addition of surfactants can effectively disperse the metal iron-molybdenum catalyst particles, prevent them from agglomerating and precipitating, improve the effective utilization rate of active metals, and also facilitate the carbon layer to be evenly coated on the catalyst surface.
[0090] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a carbon-coated iron-molybdenum catalyst, characterized in that: The following steps are involved: (1) mixing deionized water and nitric acid solution to obtain a mother liquor; Under heating and stirring conditions, adding a molybdate solution and an iron salt solution dropwise to the mother liquor, and adjusting the pH value of the system to obtain a suspension; (2) subjecting the suspension obtained in step (1) to aging and a first post-treatment in sequence to obtain a precursor; calcining the precursor to obtain iron-molybdenum oxide; (3) After mixing the carbon source and the solvent, adding the acidic solution, and performing a first stirring treatment to obtain a carbon source solution; The carbon source solution is mixed with a surfactant and the iron-molybdenum oxide obtained in step (2), and pH is adjusted, a second stirring treatment is performed, and pyrolysis is performed in sequence to obtain a pyrolysis product; The pyrolysis product is mixed with deionized water, and a third stirring treatment and a second post-treatment are performed in sequence to obtain a carbon-coated iron-molybdenum catalyst.
2. The preparation method according to claim 1, characterized in that: The pH of the mother liquor in step (1) is 1 to 6; the temperature of the heating and stirring is 25 to 90°C.
3. The preparation method according to claim 1, characterized in that: The concentrations of the molybdate solution and the iron salt solution in step (1) are independently 0.1-1.0 mol / L; the molar ratio of molybdenum in the molybdate solution to iron in the iron salt solution is (0.3-4.5):
1.
4. The preparation method according to claim 1, characterized in that: The calcination temperature in the step (2) is 200 to 650° C., and the calcination time is 2 to 7 hours.
5. The preparation method according to claim 1, characterized in that: In the step (3), the carbon source is at least one of sugars, alcohols, organic acids, aldehydes, polystyrene, polyphenols and melamine.
6. The preparation method according to claim 1, characterized in that: In the step (3), the mass ratio of iron-molybdenum oxide to carbon source aqueous solution is (0.1-1):
1.
7. The preparation method according to claim 1, characterized in that: In the step (3), the pH is adjusted by adding an alkali solution to adjust the pH of the system to 5-9; the alkali in the alkali solution is carbonate, phosphate, NaOH or NH3·H2O.
8. The preparation method according to claim 1, characterized in that: The pyrolysis temperature in step (3) is 600-1000° C., and the pyrolysis time is 1-12 hours.
9. A carbon-coated iron-molybdenum catalyst prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the carbon-coated iron-molybdenum catalyst according to claim 9 in the preparation of formaldehyde.
Citation Information
Cited By
Carbon-coated metal oxide ozone catalyst as well as preparation method and application thereof
CN121446490A